Temporal Fat Pad Volume in Patients With Thyroid Eye Disease. Issue 2 (March 2020) - Choudhary, Maria M.; Zhang, Kevin R.; Johnson, Scott; Hwang, Catherine J.; Chon, Brian H.; Perry, Julian D.
Abstract : Purpose: To determine whether thyroid eye disease (TED) is associated with a change in temporal fossa soft tissue volume. Methods: CT imaging studies were selected from patients with TED considering orbital decompression surgery and from an age-matched group of controls presenting to the Emergency Department for nontraumatic conditions requiring CT imaging. Measurements of the temporal fossa fat pad and soft tissue thickness were used as a proxy for volume and were performed using the zygomaticotemporal suture as a reference point. Categorical variables were described using frequencies and percentages, while continuous variables were described using medians and standard deviations. Chi-square tests were used to assess the relationship between gender and age group, while t -tests were used to examine the relationship between continuous variables and age group. Results: A total of 56 CT scans were evaluated, including scans from 28 patients with TED and 28 controls. The following measurements were found to be significantly larger in the TED population: left fat pad measured 5 mm above the zygomaticotemporal suture ( p = 0.012), right fat pad measured 15 mm above the suture ( p = 0.005), right soft tissue measured 15 mm above the suture ( p = 0.026), left fat pad measured 15 mm above the suture ( p = 0.006), and the left soft tissue measure 15 mm above the suture ( p = 0.032). Conclusions: Thyroid eye disease is associated with an increase in temporal fossa fat pad and soft tissue volume. These findings suggest that TED disease may produce pan-facial changes rather than changes confined to the peri-orbital region. Abstract : Thyroid eye disease is associated with increased volume of the temporal fossa fat pads and appears to affect facial structures outside of the orbital area.